PRODUCTION ELASTICITY AND INCOME ANALYSIS OF MICRO-SCALE TEMPE BUSINESSES BEFORE AND DURING THE COVID-19 PERIOD IN KUPANG CITY - Naklui, Fani Trifena; Suek, Johanna; Siubelan, Yakobus C.W.; Pellokila, Marthen Robinson (Undana Press, 2025)
MSMEs are important in the national economy, including the processed food sector such as tempeh. The purpose of this study is to analyze the production elasticity of tempeh in three MSMEs in Kupang City and to analyze the income of these three MSMEs before and during the COVID-19 pandemic. The selection of locations was purposive for three MSMEs in Kupang City, namely Nemter, Putri Tunggal, and Seumur Hidup MSMEs. The analysis was conducted quantitatively and descriptively. The data used were primary and secondary data, collected through interviews, observations, and documentation. Data analysis was conducted using production elasticity formulas and income calculation formulas. From this study, it can be concluded that the highest production elasticity before the COVID-19 pandemic was obtained in Nemter MSMEs on capital input with a value of 2.03. The production elasticity experienced in Putri Tunggal MSMEs had the highest variation in labor input with a value of 1.13 and the lowest production elasticity in capital input with a value of -0.67. Meanwhile, the highest production elasticity at UMKM Seumur Hidup was observed in raw material inputs with a value of 1.02, and the lowest production elasticity was in capital inputs with a value of -0.02. Production elasticity during the Covid-19 period in Nemter MSMEs was 1.72, the highest value for capital input, and the lowest elasticity was found in labor input at 1.23. Production elasticity in Putri Tunggal MSMEs had the highest value for capital input at 1.69 and the lowest value for raw material input at 1.01. At the Seumur Hidup SME, the highest production elasticity was observed in raw material inputs at 1.49, while the lowest was in capital inputs at -2.24. Revenue received by the Nemter SME before the COVID-19 pandemic was IDR 53,031,980, and during the pandemic, it was IDR 36,303,817. Meanwhile, the income from the Putri Tunggal SME before the COVID-19 pandemic was IDR 72,035,466 and during the COVID-19 pandemic was IDR 52,021,675. Furthermore, the income obtained by the Seumur Hidup SME before the COVID-19 pandemic was IDR 30,195,550 and during the COVID-19 pandemic was IDR 44,114,278.